Analysis of Power Generation using Waste Heat in Industries using Thermoelectric Generator - Gondane, Dr. Shubhangi; Watari, Priyanshu; Borkar, Niraj; Paramanandigiree, Niteshgiree; Dhongade, Pavan; Nagpure, Pawan; Wanjari, Rohit (International Journal of Advanced Engineering Research and Science, 2023)
Recently, increased emphasis has been placed on the global issue of rapid economic growth, a relative energy scarcity, internal combustion engine exhaust waste heat, and environmental degradation. About 30 to 40 percent of the total heat delivered to the engine in the form of fuel is transformed into meaningful mechanical work. It is necessary to convert waste heat into usable work since the leftover heat is released into the environment through exhaust gases and engine cooling systems, leading to an increase in entropy and major environmental degradation. Due to the specific advantages of thermoelectric generators, they have emerged as a possible alternative green technology as waste heat recovering techniques like the thermoelectric generator (TEG) are developed. A techniquethat can directly convert the thermal energy found in exhaust gas into electric power is the subject of the majority of current study. In this research, a thermoelectric power generator based on exhaust gas was developed for industrial use. The exhaust gases in the pipe serve as the thermoelectric power generator's heat source. As a result, this study suggests and puts into practice a thermoelectric waste heat energy recovery system using the exhaust heat from running equipment. The goal of the project is to directly transform the heat energy from vehicle waste heat to electrical energy using a thermoelectric generator. Although the largest amount of electric power produced by such a system is just 10 W from a single TEG module, significant advancements in material science can make the ambitious aim of generating larger wattages by any means a real possibility.